2001
DOI: 10.1177/002193470103100402
|View full text |Cite
|
Sign up to set email alerts
|

The Nguzo Saba as a Foundation for African American College Student Development Theory

Abstract: Predominantly Euroamerican colleges and universities were founded with the intent of educating the White middle class. They are based on Anglo-Saxon, Euroamerican values and survive because they are related to the cultural values of the broader American society (McEwen, Roper, Bryant, & Langa, 1996).Because educators at predominantly White institutions have historically relied upon a body of knowledge that supports and reinforces Euroamerican values, they often prove unsuccessful in responding to the education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 6 publications
0
23
0
Order By: Relevance
“…Use of Nguzo Saba principles in mental health interventions with African Americans show benefits in resolving psychosocial issues (Franklin & Pack-Brown, 2001; Mclean & Marini, 2003). Also, use of Nguzo Saba principles in education interventions resulted in increased high school grade point average, improved behaviors at school and attitudes toward school, and increased interest in personal and social growth, as well as aspirations for success (Johnson, 2001; Wyatt, 2009). These positive results were influential in our decision to use Nugzo Saba in the OHDC.…”
Section: Oh Happy Day Classmentioning
confidence: 99%
“…Use of Nguzo Saba principles in mental health interventions with African Americans show benefits in resolving psychosocial issues (Franklin & Pack-Brown, 2001; Mclean & Marini, 2003). Also, use of Nguzo Saba principles in education interventions resulted in increased high school grade point average, improved behaviors at school and attitudes toward school, and increased interest in personal and social growth, as well as aspirations for success (Johnson, 2001; Wyatt, 2009). These positive results were influential in our decision to use Nugzo Saba in the OHDC.…”
Section: Oh Happy Day Classmentioning
confidence: 99%
“…Thus, it implores student affairs professionals and administrators to examine what African American college students say about themselves, psychologically and socially (Johnson, 2001). Hence, it serves as a step in transcending long-established student development theories that are rooted in European psychology (McEwen et al, 1996).…”
Section: African American Student Adjustmentmentioning
confidence: 99%
“…These seven principles in Swahili and English are: "(1) Umoja (Unity); (2) Kujichaguila (Self-Determination); (3) Ujima (Collective Work and Responsibility); (4) Ujamaa (Cooperative Economics); (5) Nia (Purpose); (6) Kuumba (Creativity); and (7) lmani (Faith)" (Karenga, 1993, p. 173-4). Derived from the tenets of the African American holiday of Kwanzaa (developed out of Kawaida, meaning culture and reason, which celebrates the Nguzo Saba), it represents a grand departure from many college adjustment theories that are bastions of Eurocentrism, assimilation, and conservatism (Johnson, 2001;McEwen et al, 1996;Tinto, 1993). According to Karenga (1993), the Nguzo Saba represents a community-centered approach to building togetherness, social consciousness, and more affable moral precepts.…”
Section: African American Student Adjustmentmentioning
confidence: 99%
“…Thus, the result of the normalcy of African American college students will be based on how far they have been removed from what should be their natural way of viewing the world and whether or not programs and services help them find their way there. Johnson (2001) suggested that one approach to developing programs that address the psychosocial developmental needs of African American college students is to base them on the Nguzo Saba (seven principles) of Kwanzaa. The seven principles, or Nguzo Saba, allow for the incorporation of authentic African Americanbased values into the development of African American college students (Johnson, 2001).…”
Section: Research Implicationsmentioning
confidence: 99%